Ceramic coating based on prefabricated coating and micro-arc sintering, preparation method and application
By using prefabricated coating and microarc sintering methods in microarc oxidation technology, the problems of high energy consumption and poor performance regulation of microarc oxidation technology are solved, and rapid and low-energy-consuming ceramic coating preparation is achieved, and coating is improved. The density and performance regulation of the layer are suitable for aerospace and other fields.
Patent Information
- Application Number
- CN202411302451.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
The existing microarc oxidation technology consumes a high energy consumption, and most of the energy is transferred to the electrolyte in the form of heat. The actual energy used for electrochemical film formation accounts for very little. In the existing technology, the electrolyte composition or nanometers are adjusted. The method of increasing the growth rate of coatings by adding particles is limited in effect and lacks performance regulation.
Using a ceramic coating preparation method based on prefabricated coating and microarc sintering, a slurry is formed by mixing ceramic powder, water glass and water, coated on a metal matrix for drying, and then undergoing microarc oxidation treatment in the electrolyte. Ceramic particles in the prefabricated coating are sintered under the action of plasma, and the current density, frequency and duty cycle are adjusted to control the density and uniformity of the coating.
It significantly shortens the preparation time and energy consumption of microarc oxidation coatings, improves the density and performance regulation of ceramic coatings, realizes the preparation of coatings with a thickness of more than 300μm in half an hour, and reduces the overall energy consumption. It has various properties such as wear resistance, corrosion resistance, and high temperature resistance.
Smart Images

Figure CN119162629A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal surface protection, and in particular relates to a ceramic coating based on prefabricated coating and micro-arc sintering, a preparation method and application thereof. Background Art
[0002] MicroArc Oxidation (MAO), also known as Plasma Electrolytic Oxidation (PEO), is a surface modification technology that uses high-voltage micro-arc discharge to prepare ceramic coatings on the surfaces of metals such as Al, Mg, Ti, and Zr immersed in an electrolyte. The high-temperature plasma generated by the micro-arc discharge process can sinter the components in the electrode liquid into the coating. Therefore, by artificially designing the electrolyte composition, the micro-arc oxidation coating can be given specific wear resistance, corrosion resistance, high temperature resistance, catalysis, and biocompatibility. At present, this technology has become one of the hot spots in international material research and is widely used in aerospace, weapon equipment, transportation, shipbuilding, textiles, and electronics industries. However, the energy consumption of the micro-arc oxidation process is extremely high (5-600kW / dm 2 Compared with similar anodizing technologies, the energy consumption is only 150W / dm 2 ) limits the large-scale application of this technology.
[0003] In order to reduce the energy consumption of micro-arc oxidation technology, increasing the growth rate of ceramic coatings is the only means at present. So far, most of the research has been on increasing the growth rate of ceramic coatings by significantly increasing the concentration of film-forming substances in the electrolyte (silicates, aluminates, nanoparticles, etc.); the main problems existing in the existing technology are that the existing micro-arc oxidation technology has high energy consumption, and most of the energy is transferred to the electrolyte in the form of heat, and the energy actually used for electrochemical film formation accounts for a very small proportion; the method of increasing the growth rate of coatings by adjusting the electrolyte composition or the amount of nanoparticles added in the existing technology has limited effect, and the actual utilization rate of nanoparticles is not high; the method of prefabricating anodized films in the existing technology and then performing micro-arc oxidation does not have the composition and performance controllability of micro-arc oxidation coatings. Summary of the invention
[0004] In view of the problems and defects of the prior art, the present invention provides a method for preparing a ceramic coating based on a prefabricated coating and micro-arc sintering, comprising the following steps:
[0005] S1: Mix ceramic powder, water glass and water, stir evenly, and perform ultrasonic degassing to obtain slurry;
[0006] S2: coating the slurry obtained in S1 on the surface of a metal substrate, drying and dehydrating the slurry to obtain a metal substrate covered with a prefabricated coating;
[0007] S3: The metal covered with the prefabricated coating in S2 is used as the anode and the stainless steel is used as the cathode, and placed in the electrolyte for micro-arc oxidation treatment. After the treatment, the anode is taken out for cleaning to obtain a micro-arc oxidation ceramic coating.
[0008] Furthermore, the ceramic powder described in S1 accounts for 20-50wt%, water glass accounts for 50-80wt%, and pure water accounts for 3%-15wt%.
[0009] Furthermore, the particle size of the ceramic powder described in S1 is 200-500 nm.
[0010] Furthermore, the drying temperature in S2 is 100-160° C., and the drying time is 0.5-2 hours.
[0011] Furthermore, the parameters adjusted during the micro-arc oxidation treatment in S3 include the positive current being set to 10-20 A / dm 2 ; Negative current is set to 10-20A / dm 2 ; The frequency is set to 200-1000Hz; The duty cycle is set to 50%-80%.
[0012] Furthermore, the electrolyte described in S3 includes sodium hydroxide solution and sodium silicate, the concentration of sodium hydroxide is 1-5 g / L, and the concentration of sodium silicate is 5-10 g / L.
[0013] Furthermore, the electrolyte temperature in S3 is 10-40°C; and the micro-arc oxidation time is 5-20 minutes.
[0014] A ceramic coating based on prefabricated coating and micro-arc sintering,
[0015] The invention discloses an application of a ceramic coating based on a prefabricated coating and micro-arc sintering, wherein the ceramic coating based on the prefabricated coating and micro-arc sintering is applied in the preparation of aerospace materials.
[0016] Technical Effects
[0017] (1) The present invention provides a ceramic coating based on prefabricated coating and micro-arc sintering. The prefabricated coating method can firmly bond various ceramic particles required for the growth of micro-arc oxidation coating to the metal surface.
[0018] (2) The present invention provides a method for preparing a ceramic coating based on a pre-coating and micro-arc sintering. By selecting a suitable ratio of ceramic particles, water glass and water, the ceramic particles can be evenly dispersed in the slurry, so that the pre-coating has a more uniform and dense structure and good alkali resistance. In this way, the pre-coating will not fall off over a large area during the micro-arc oxidation process. In addition, the fluidity of the ceramic slurry can be changed by adjusting the above ratio, so that the thickness and uniformity of the pre-coating can be adjusted. When the pre-coating is sintered by the plasma during the micro-arc oxidation process, a uniform and dense ceramic coating can be quickly formed. And by adjusting the type, particle size and ratio of the ceramic particles in the pre-coating, the performance of the final coating can be controlled to form a coating with different functions.
[0019] (3) The present invention provides a method for preparing a ceramic coating based on a prefabricated coating and micro-arc sintering. The method of the present invention significantly shortens the preparation time and energy consumption of the micro-arc oxidation coating by combining the prefabricated coating with micro-arc sintering. The traditional micro-arc oxidation method requires a long time or extremely high current density to form a coating of the required thickness, while the present method can prepare a coating with a thickness of more than 300 μm within half an hour, and the current density is only a conventional value, which greatly improves production efficiency. The traditional micro-arc oxidation technology has high energy consumption, mainly because a large amount of electrical energy is converted into heat. The method of the present invention utilizes the presence of the prefabricated coating to use the heat generated during the micro-arc oxidation process to sinter ceramic particles, thereby shortening the coating preparation time and reducing overall energy consumption.
[0020] (4) The present invention provides an application of a ceramic coating based on a prefabricated coating and micro-arc sintering. The coating has multiple properties such as wear resistance, corrosion resistance, and high temperature resistance, and can be applied to aerospace, shipbuilding, transportation and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0022] Figure 1 (A) cross-section and (B) surface morphology of a prefabricated alumina ceramic coating bonded with water glass according to Example 1 of the present invention;
[0023] Figure 2 (A) cross-section and (B) surface morphology of the prefabricated coating after micro-arc oxidation treatment for 20 minutes in Example 1 of the present invention;
[0024] Figure 3(A) cross section and (B) surface morphology of a micro-arc oxidation coating prepared on a pure aluminum surface without a pre-coating under the same micro-arc oxidation process as in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with Examples 1-3 of the present invention and the attached Figures 1 to 3 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Compared with traditional electrochemical conversion film technology, the occurrence of micro-arc oxidation requires the breakdown voltage of the oxide film on the metal surface (400-600V). The process of electrical breakdown generates plasma to deposit and sinter the film-forming materials in the oxide film and the surrounding electrolyte to finally form a micro-arc oxidation coating. The energy utilization rate of this process is not high, and a large amount of electrical energy is converted into heat for heating the electrolyte. Considering the location of electrical breakdown (metal surface) and triggering conditions (passivation film with high impedance), artificially prefabricating a high-impedance ceramic coating on the surface of the metal substrate can quickly induce plasma electrical breakdown during micro-arc oxidation to sinter the prefabricated ceramic coating. Since high-voltage electrical breakdown occurs preferentially in weak areas of the coating, as micro-arc oxidation proceeds, the density of the coating will continue to increase, and the ceramic particles in the prefabricated coating can provide raw materials for the growth of the micro-arc oxidation coating. When the ceramic particles in the prefabricated coating are completely clad together, the coating preparation process is completed.
[0027] In the preparation process of the prefabricated coating, in order to bond the ceramic particles together, we selected water glass as a bonding agent (sodium silicate is a commonly used component of micro-arc oxidation electrolyte). The Si-O-Si bond formed after the water glass and ceramic particles are fully solidified has a certain strength and alkali resistance. The use of nano-scale ceramic particles makes the prefabricated coating more dense and difficult for the electrolyte to penetrate. The above makes the prefabricated coating not dissolve in a short time after being immersed in the alkaline micro-arc oxidation electrolyte, which is convenient for subsequent micro-arc oxidation treatment.
[0028] Example 1
[0029] S1; 15 g of alumina ceramic powder with a particle size of 300 nm, 30 g of water glass, and 5 g of water were mixed, and then stirred evenly with a stirrer, and ultrasonically degassed for 10 min to form a uniform slurry;
[0030] S2: The slurry obtained in S1 is then evenly coated on the surface of the metal substrate with a coating thickness of 90 μm, and the coated metal is then placed in a drying oven for dehydration; the drying temperature is set to 100°C and the drying time is set to 0.5 hours to ensure that the water glass is fully cured and the coating is initially fixed on the metal substrate to obtain a metal substrate covered with a prefabricated coating.
[0031] S3: The coated metal obtained in S3 was used as the anode and the stainless steel was used as the cathode in the electrolyte for conventional micro-arc oxidation treatment. The micro-arc oxidation parameters included: the positive current was set to 10A / dm 2 ; Negative current is set to 10A / dm 2 ; The frequency is set to 200 Hz; The duty cycle is set to 50%; The electrolyte consists of sodium silicate and sodium hydroxide solution, the sodium silicate concentration is 5 g / L, and the sodium hydroxide concentration is 1 g / L; The electrolyte temperature is set to 10°C; The micro-arc oxidation time is set to 20 min; After the micro-arc oxidation is completed, the anode product is taken out and washed with clean water to obtain a micro-arc oxidation ceramic coating.
[0032] Combination Figure 1 The cross-section and surface morphology of the prefabricated alumina ceramic coating bonded with water glass can be obtained. Figure 2 The cross-section and surface morphology of the prefabricated coating after micro-arc oxidation treatment for 20 minutes can be obtained. Figure 3 The cross-section and surface morphology of the micro-arc oxidation coating prepared on the pure aluminum surface without pre-coating under the same micro-arc oxidation process can be obtained.
[0033] Example 2
[0034] S1; 20 g of zirconia ceramic powder with a particle size of 500 nm, 30 g of water glass and 2 g of water were mixed, and then stirred evenly with a stirrer, and ultrasonically degassed for 10 min to form a uniform slurry;
[0035] S2: The slurry obtained in S1 is then evenly coated on the surface of the metal substrate with a coating thickness of 300 μm, and the coated metal is then placed in a drying oven for dehydration; the drying temperature is set to 160°C and the drying time is set to 2 hours to ensure that the water glass is fully cured and the coating is initially fixed on the metal substrate to obtain a metal substrate covered with a prefabricated coating.
[0036] S3: The coated metal obtained in S3 was used as the anode and the stainless steel was used as the cathode in the electrolyte for conventional micro-arc oxidation treatment. The micro-arc oxidation parameters included: the positive current was set to 20A / dm 2 ; Negative current is set to 20A / dm 2The frequency is set to 1000 Hz; the duty cycle is set to 80%; the electrolyte consists of sodium silicate and sodium hydroxide solution, the sodium silicate concentration is 10 g / L, and the sodium hydroxide concentration is 5 g / L; the electrolyte temperature is set to 40°C; the micro-arc oxidation time is set to 20 min; after the micro-arc oxidation is completed, the anode product is taken out and washed with clean water to obtain a micro-arc oxidation ceramic coating.
[0037] Example 3
[0038] S1; 15 g of alumina ceramic powder with a particle size of 300 nm, 45 g of water glass and 1 g of water were mixed, and then stirred evenly with a stirrer, and ultrasonically degassed for 10 min to form a uniform slurry;
[0039] S2: The slurry obtained in S1 is then evenly coated on the surface of the metal substrate with a coating thickness of 150 μm, and the coated metal is then placed in a drying oven for dehydration; the drying temperature is set to 130°C and the drying time is 1 hour to ensure that the water glass is fully cured and the coating is initially fixed on the metal substrate to obtain a metal substrate covered with a prefabricated coating.
[0040] S3: The coated metal obtained in S3 was used as the anode and the stainless steel was used as the cathode in the electrolyte for conventional micro-arc oxidation treatment. The micro-arc oxidation parameters included: the positive current was set to 15A / dm 2 ; Negative current is set to 15A / dm 2 ; The frequency is set to 500 Hz; The duty cycle is set to 65%; The electrolyte consists of sodium silicate and sodium hydroxide solution, the sodium silicate concentration is 8 g / L, and the sodium hydroxide concentration is 3 g / L; The electrolyte temperature is set to 20°C; The micro-arc oxidation time is set to 10 min; After the micro-arc oxidation is completed, the anode product is taken out and washed with clean water to obtain a micro-arc oxidation ceramic coating.
[0041] In the present invention, by adjusting the current density, the intensity and temperature of the plasma generated by the micro-arc discharge can be controlled, thereby affecting the compactness and uniformity of the coating: when the current density is too low, the plasma temperature is not enough to melt and sinter the nano-ceramic particles in the prefabricated coating; when the current density is too high, the prefabricated coating is easily locally ablated, and the prepared coating has poor uniformity; a higher current density helps to accelerate the growth of the coating, but may increase energy consumption. It has been found through experiments that 10-15A / dm 2 Positive current density and 10-15A / dm 2 Negative current density can achieve the best balance between energy consumption and coating quality.
[0042] Frequency affects the discharge cycle and plasma formation. Higher frequencies can increase the uniformity and stability of the discharge. Through experiments, we found that the frequency range of 400-600Hz can improve coating quality while controlling energy consumption. As for the duty cycle, the duty cycle determines the proportion of time that power is on in each discharge cycle. A higher duty cycle helps to form a dense coating, but may cause local overheating. Experiments show that a duty cycle of 60%-70% can achieve a good balance between coating quality and preventing overheating.
[0043] As for the electrolyte composition, traditional micro-arc oxidation increases the coating growth rate by adding electrolyte additives and increasing the component concentration (the improvement effect is limited). In the present invention, although the traditional micro-arc oxidation electrolyte control idea is still effective, the method of preparing the coating by prefabricated coating and micro-arc sintering adopted in the present invention provides a new idea for coating thickness and performance control, and abandons the traditional method of optimizing the electrolyte components. In the present invention, only basic electrolyte components are required to achieve the electrochemical environment required for micro-arc discharge. Of course, the electrolyte composition still has an impact on the coating growth process in the present invention: if the pH value of the electrolyte is too high, the prefabricated coating will fall off quickly after being immersed in the electrolyte (the solidified water glass coating is not resistant to strong alkali), and subsequent sintering cannot be performed; if the content of film-forming components in the electrolyte is too low (negatively charged colloids, such as silica gel), the prefabricated coating will be unable to repair the discharge channel in time after being electrically broken down, resulting in an increase in coating defects. Through experiments, we determined that the combination of 8g / L sodium silicate and 2g / L sodium hydroxide can achieve the best effect between coating growth rate and quality.
[0044] The electrolyte temperature affects the stability of the discharge process and the uniformity of the coating. Experiments show that the best coating quality and stable discharge process can be obtained by controlling the temperature within the range of 20-30°C. As for the micro-arc oxidation time, this is related to the thickness of the pre-coating. The thicker the pre-coating, the longer the sintering time required. For a 100-200μm thick pre-coating, the time is controlled within 10-15 minutes, which can minimize energy consumption and processing time while ensuring the coating quality.
[0045] The selection of components in the preparation method also requires creative thinking and work. In the selection of binders, the important component of water glass (sodium silicate) is an important component of traditional micro-arc oxidation electrolytes. Using water glass as a binder will not introduce additional components to the micro-arc oxidation coating and affect its performance. Other inorganic / organic adhesives cannot achieve such an effect; water glass and the hydroxyl groups on the surface of ceramic particles can form a solid network structure after dehydration and condensation, so that it remains stable and does not fall off under the action of micro-arc electric breakdown. The utilization rate of nano-ceramic particles is improved. Compared with other curing methods, the heating curing method selected for the curing of water glass is the simplest and most controllable. The curing temperature needs to be strictly controlled. If the temperature is too low, the strength and alkali resistance of the prefabricated coating will be insufficient. If the temperature is too high, the prefabricated coating will bubble.
[0046] As for ceramic particles, to induce micro-arc discharge, the prefabricated coating must have a high impedance, so non-conductive ceramic particles are selected; there are strict requirements for the particle size of ceramic particles. If the particle size is too large, the fluidity of the slurry is poor, the thickness of the prefabricated coating is too high, the uniformity is poor, and the ceramic particles are difficult to be melted under the action of plasma, and the final coating has many defects and poor quality. If the particle size is too small, the ceramic particles are easy to agglomerate and difficult to disperse in water glass, and the cost of ceramic powder increases. Preferably, 200-500nm ceramic powder is most suitable.
[0047] The present invention provides a method for preparing a ceramic coating based on a prefabricated coating and micro-arc sintering, which combines the prefabricated coating with the micro-arc sintering process. By prefabricating a ceramic coating on a metal substrate and sintering these prefabricated coatings using plasma during micro-arc oxidation, rapid preparation and optimization of the coating is achieved. This method not only improves the density of the coating, but also significantly shortens the preparation time and reduces energy consumption. In addition, by combining different ceramic particles and adjusting the thickness of the prefabricated coating, unexpected performance gradients and functionality can be achieved in the coating, which is not achievable with conventional technologies.
[0048] The present invention provides a method for preparing a ceramic coating based on a pre-coating and micro-arc sintering, which not only achieves a breakthrough in improving the growth rate and density of the coating, but also finds that the chemical bonding effect between the pre-coating and the substrate during the micro-arc oxidation process is very good. This bonding significantly improves the stability of the coating, so that the pre-coating does not fall off under the erosion of alkali solution and the bombardment of the arc, ensuring the efficient cladding of the ceramic particles in the pre-coating. In addition, the method can adjust the performance of the final coating according to the composition of the pre-coating, and realizes precise control of the coating performance. These effects exceed the expectations of traditional micro-arc oxidation technology.
[0049] By optimizing the selection of binders, the combination of water glass and ceramic particles, the preparation steps of prefabricated coatings, and various parameters in the micro-arc sintering process, we have achieved remarkable innovative results in improving coating quality, shortening preparation time, reducing energy consumption, and achieving performance regulation. These technological breakthroughs do not rely on the inherent effects of the products themselves in existing technologies, but are achieved through our unique methods and optimization steps.
Claims
1. A method for preparing a ceramic coating based on prefabricated coating and micro-arc sintering, characterized in that: The following steps are involved: S1: Mix ceramic powder, water glass and water, stir evenly, and perform ultrasonic degassing to obtain slurry; S2: coating the slurry obtained in S1 on the surface of a metal substrate, drying and dehydrating the slurry to obtain a metal substrate covered with a prefabricated coating; S3: The metal covered with the prefabricated coating in S2 is used as the anode and the stainless steel is used as the cathode, and placed in an electrolyte for micro-arc oxidation treatment. After the treatment, the anode is taken out for cleaning to obtain a micro-arc oxidation ceramic coating.
2. The method for preparing a ceramic coating based on prefabricated coating and micro-arc sintering according to claim 1, characterized in that: The ceramic powder described in S1 accounts for 20-50wt%, water glass accounts for 50-80wt%, and pure water accounts for 3%-15wt%.
3. The method for preparing a ceramic coating based on prefabricated coating and micro-arc sintering according to claim 1, characterized in that: The particle size of the ceramic powder described in S1 is 200-500 nm.
4. The method for preparing a ceramic coating based on prefabricated coating and micro-arc sintering according to claim 1, characterized in that: The drying temperature in S2 is 100-160°C, and the drying time is 0.5-2 hours.
5. The method for preparing a ceramic coating based on prefabricated coating and micro-arc sintering according to claim 1, characterized in that: The parameters adjusted during the micro-arc oxidation process in S3 include the positive current set to 10-20A / dm 2 ; Negative current is set to 10-20A / dm 2 ; The frequency is set to 200-1000Hz; The duty cycle is set to 50%-80%.
6. The method for preparing a ceramic coating based on prefabricated coating and micro-arc sintering according to claim 1, characterized in that: The electrolyte described in S3 includes sodium hydroxide solution and sodium silicate, the concentration of sodium hydroxide is 1-5g / L, and the concentration of sodium silicate is 5-10g / L.
7. The method for preparing a ceramic coating based on prefabricated coating and micro-arc sintering according to claim 1, characterized in that: The electrolyte temperature in S3 is 10-40°C; the micro-arc oxidation time is 5-20 minutes.
8. A ceramic coating based on prefabricated coating and micro-arc sintering obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The ceramic coating based on prefabricated coating and micro-arc sintering has a double-layer structure, including an inner micro-arc oxidation layer grown by in-situ electrochemical growth and an outer micro-arc cladding layer.
9. The use of a ceramic coating based on prefabricated coating and micro-arc sintering according to claim 8, characterized in that: The ceramic coating based on prefabricated coating and micro-arc sintering is used in the preparation of aerospace materials.
